Harmonisation of Shari ‘ah and International law In Protecting the Rights of Orphans: special reference to Convention on the Rights of the Child 1989 - Razzaq, Munazza (2023)
This paper explores the importance of protecting children, especially orphans, who are considered valuable assets in human life. Children are an integral part of families and communities and a source of joy and happiness for their families and nations. Therefore, it is essential to safeguard them from all forms of harm and injustice. Islamic law provides a comprehensive legal system that aims to protect and promote the well-being of children, including orphans. This study investigates the specific provisions within Islamic law that address the rights of orphans and compares them with international legal documents, particularly the Convention on the Rights of the Child 1989 (the CRC). For this research, it explores several rights of orphans under the CRC and the Shari’ah, namely the rights to life, the rights to care and upbringing (kafalah), the rights to name and identity, the health rights, the rights to education and the rights to profess a religion. The research will further examine the extent of harmonisation between these two legal systems while also identifying their differences. The research methodology is primarily qualitative, relying on a doctrinal approach and utilizing primary and secondary sources in the library. The expected outcome of this research is to identify common principles regarding protecting orphans' rights, as outlined in Islamic law (the Shari’ah) and international conventions. Additionally, the study will propose potential avenues for harmonising these two legal systems in relevant and necessary areas.